2022
DOI: 10.1021/acs.jproteome.1c00926
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Microproteins in Hep3B Cells at Different Cell Cycle Stages

Abstract: Microproteins are generated from small open reading frames and turn out to play various vital biological functions. As an essential biological event of eukaryotic cells, the cell cycle is involved in cell replication and division. For such a highly regulated event, microproteins associated with cell cycle regulation remained unclarified. Utilizing a combination of bottom-up and top-down proteomics, we analyzed microproteins at specific cell cycle stages of Hep3B cells. A total of 657 microproteins were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This research study was performed using UHPLC-QTOF-MS, a novel platform of mass spectrometry technology with a high level of identification and profiling of metabolites and proteins in complex samples. Although previous studies had revealed metabolic and proteomic changes in Hep3B cells [ 22 , 23 , 24 ] there is no metabolomics and proteomics study to date that has comparatively profiled the metabolomic and the proteomic composition of parental and resistant Hep3B cell lines via UHPLC-QTOF-MS analysis to study drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This research study was performed using UHPLC-QTOF-MS, a novel platform of mass spectrometry technology with a high level of identification and profiling of metabolites and proteins in complex samples. Although previous studies had revealed metabolic and proteomic changes in Hep3B cells [ 22 , 23 , 24 ] there is no metabolomics and proteomics study to date that has comparatively profiled the metabolomic and the proteomic composition of parental and resistant Hep3B cell lines via UHPLC-QTOF-MS analysis to study drug resistance.…”
Section: Introductionmentioning
confidence: 99%